PERTINENT ILLS CONCOMITANT WITH MATRIFOCALITY IN ZIMBABWE: IMPLICATIONS FOR DEVELOPMENT - MAFA, ITAI (Innovare Journal of Social Sciences, 2021)
Objective: The paper explored the challenges underpinning matrifocality in Zimbabwe, what is normally termed single motherhood. With the marital institution losing eminence in Africa due to a myriad of factors such as globalization, industrialization, and eurocentrism; this has greatly altered today’s family structure. The study was anchored on the realization that the traditional composition of an African family which recognized extended families has now been overshadowed by the surfacing of nuclear families as well as an increase in matrifocal families. Methods: The article utilized a qualitative approach and a case study design. Convenience sampling was used to select 16 single mothers and a purposive sampling method was preferred to sample three key informants. For single mothers, in a mini-depth interviews were used to elicit detailed information and focus group discussion was adopted for key informants. Data were analyzed using the thematic process to integrate the findings. Results: Stress-induced pathologies, relational conflict within the family set-up, economic privations, communal cynicism, and ostracism were identified as challenges compromising the development and stability of matrifocal families in Chiredzi district. Conclusions: Guided by various feminism lenses and the ecological perspective, the article shifts from the pathological view to single motherhood, advocating for the need to focus the dialogue along the challenges faced by matrifocal families in an attempt to recommend interventions that can strengthen this family set-up.